The influence of Asymmetric Inflow Reconnection on the Diffusion Region in Resistive Space Plasmas - Hossein Lotfi; Mahboub Hosseinpour (Iranian Journal of Astronomy and Astrophysics)
To investigate the effect of asymmetric magnetic reconnection on thedevelopment of the diffusion region and growth of magnetic islands induced duringreconnection (plasmoids), we use 2-dimensional resistive magnetohydrodynamics sim-ulations. In particular, we consider the strength of the magnetic field and plasma massdensity to be dissimilar on both sides of the current sheet. For three cases, the resultsshow that the initial X-point position shifts from the center of the diffusion region tothe stronger magnetic field while the plasmoids grow toward the weaker magnetic field.Also, the increase of asymmetry in the magnetic field and plasma mass density leads tothe reconnection rate and the growth time of plasmoid instability becoming less. Dueto the displacement of reconnection sites in asymmetric cases, the output momentumfrom these sites does not directly collide with the outflow jets, so the velocity of theoutflow jets is lower than in the symmetric case.